Growth of Morus alba L. under water deficit conditions - Karatassiou M.; Parissi Z.M.; Abraham E.M.; Kyriazopoulos A.P. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Morus alba is a high quality and forage species, recently introduced in the Mediterranean rangelands. The effects of water stress on growth parameters of M. alba were studied. M. alba seedlings were planted under a transparent shelter. Three irrigation levels (100%, 50%, and 25% of water-holding capacity) were applied. Half of the plants were cut at 30% of their current stem length at the end of May. Water potential (?) and relative water content (RWC) were measured every 15 days. Additionally, leaf and stem growth rates were estimated. The cutting plants maintained more favourable water balance in the leaf tissue than the control. ? in plants subject to the cutting treatment decreased as the water stress increased, whereas the plants in 100% water-holding capacity had higher ? and lower LGR/SGR ratio. These results suggest that M. alba could develop specific adaptation and growth mechanisms under water deficit conditions.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)